2011
DOI: 10.1007/s10653-011-9441-z
|View full text |Cite
|
Sign up to set email alerts
|

The concentration and distribution of organochlorine pesticides in the air from the karst cave, South China

Abstract: Organochlorine pesticides (OCPs) in the air of Dayan Cave in Guilin were analyzed, to investigate the source and contamination levels. Generally, air outside of the cave had much higher concentrations than inside air, and both outside and inside air showed much lower contamination levels than those observed in other regions in China and abroad. The ratios of α-/γ-HCHs and the percentages of β-(or δ-)HCH implied a residue of historical local technical HCH contamination. The DDT concentrations, o,p'-DDT/p,p'-DDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This is unexpected because the agricultural use of technical DDT was banned in 1983, and its exception use for vector-control was also banned in 2009 in China [ 52 ]. The fresh input of technical DDT was also found in the air from a karst cave in Guilin [ 59 ], and in the soil from Chongqing, southwestern China [ 32 ]. Results herein implied the illegal use of technical DDT, and therefore insufficient pesticide management in the study area [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is unexpected because the agricultural use of technical DDT was banned in 1983, and its exception use for vector-control was also banned in 2009 in China [ 52 ]. The fresh input of technical DDT was also found in the air from a karst cave in Guilin [ 59 ], and in the soil from Chongqing, southwestern China [ 32 ]. Results herein implied the illegal use of technical DDT, and therefore insufficient pesticide management in the study area [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al investigated the concentration and distribution of OCPs in air from the Kast cave (Dayan cave) in Guilin and showed that OCPs were detected in the air from the Dayan cave despite of the cave's relatively closed space. 11 Zhang et al investigated the distribution and sources of OCPs in the surface sediments of Lijiang River and showed that the contamination of OCPs in the sediments was at a medium level compared to the other studied rivers, and the sources of hexachlorocyclohexane and dichlorodiphenyltrichloroethane are long-term migration and historical usage. 12 In our previous study, the agricultural sewage carrying OCPs flows into the ponds around Qingshitan Reservoir and finally reaches the reservoir through the streams.…”
Section: Introductionmentioning
confidence: 99%